Gerakan dan Gagasan Islam Nusantara di Negara Indonesia - Muhammad Zein Damanik; Putri Raj Wulandari Nasution; Rizky Okctaviana (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The entry and development of Islam in Indonesia has brought changes in many aspects of people's lives from the past to the present. Modernization and globalization eliminate the diversity of regional cultures while dominating regional cultures through global capitalism in the form of Westernization through the export of goods, values, and priorities. This research aims to examine Islamic movements and ideas in the archipelago. This research uses a qualitative approach method using literature study analysis, namely analyzing various relevant literature and sources regarding Islamic movements and ideas in the archipelago. The results show that Social and humanitarian engagement of liberal Islam encourages the active involvement of Muslims in social news, such as poverty, human rights, and the environment. Organizations such as Muhammadiyah and Nahdlatul Ulama are involved in a wide range of social activities that reflect the values of social justice taught in Islam. This involvement shows that the teachings of Islam can be applied to improve the welfare of the people as a whole.